Answer:
1st option
Step-by-step explanation:
let y = f(x) and rearrange making x the subject
y = 2x + 1 ( subtract 1 from both sides )
y - 1 = 2x ( divide both sides by 2 )
= x
Change y back into terms of x with x being the inverse h(x)
h(x) = = x -
1 - 9
2 -28
3 54
4 -100
5 -60
6 0
7 49
8 -135
9 -96
10 300
11 0
12 192
9514 1404 393
Answer:
68 4/7 miles/hour
Step-by-step explanation:
The unit rate is found by dividing miles by hours:
(120 miles)/(7/4 hours) = 480/7 miles/hour = 68 4/7 miles/hour